Endophthalmitis as a complication of protozoan-fungal keratitis in a contact lens wearer: a case report - Sarnat-Kucharczyk, Monika; Filipek, Erita; Wojcik-Niklewska, Bogumila; Barchanowska, Dorota; Mrukwa-Kominek, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2022)
Introduction: Contact lens wearers who do not follow proper eye hygiene are at risk of sight-threatening protozoan keratitis, which can be complicated by fungal keratitis. If timely and proper treatment is instituted, the progression of infection can be stopped and serious ocular complications can thus be prevented. Acanthamoeba keratitis is often associated with contact lens wear. However, to our best knowledge, its coexistence with Fusarium has not been reported in a pediatric contact lens wearer. Case presentation: The aim of the paper is to present a case report of severe protozoan-fungal keratitis in a contact lens wearer. Despite delayed but intensive antiprotozoan, antifungal treatment and corneal transplantation, corneal ulceration resulted in endophthalmitis. The subsequent intervention, i.e., a combination of vitrectomy and corneal transplantation, failed to prevent the spread of infection. As the condition was considered to be life-threatening, a decision was made to perform evisceration. Conclusions: Improper eye hygiene by contact lens wearers promotes the development of corneal infections. Late diagnosis and proper but delayed treatment caused spread of the infection and severe ocular complications.